2013
DOI: 10.1007/978-3-319-03680-9_4
|View full text |Cite
|
Sign up to set email alerts
|

Protein Fold Recognition Using an Overlapping Segmentation Approach and a Mixture of Feature Extraction Models

Abstract: Protein Fold Recognition (PFR) is considered as a critical step towards the protein structure prediction problem. PFR has also a profound impact on protein function determination and drug design. Despite all the enhancements achieved by using pattern recognitionbased approaches in the protein fold recognition, it still remains unsolved and its prediction accuracy remains limited. In this study, we propose a new model based on the concept of mixture of physicochemical and evolutionary features. We then design a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Among all these methods, pseudo amino acids composition has attained the best results to extract local information Wan et al, 2013;Esmaeili et al, 2010;Chou, 2001Chou, , 2005Chou, , 2011. In the present study, we extend the concept of segmented distribution features as described in the previous subsection to compute the auto covariance features from the segmented protein sequence (Dehzangi et al, 2013d). This is done to enforce local discriminatory information extracted from PSSM.…”
Section: Segmented Auto Covariance (Pssm-sac)mentioning
confidence: 96%
See 1 more Smart Citation
“…Among all these methods, pseudo amino acids composition has attained the best results to extract local information Wan et al, 2013;Esmaeili et al, 2010;Chou, 2001Chou, , 2005Chou, , 2011. In the present study, we extend the concept of segmented distribution features as described in the previous subsection to compute the auto covariance features from the segmented protein sequence (Dehzangi et al, 2013d). This is done to enforce local discriminatory information extracted from PSSM.…”
Section: Segmented Auto Covariance (Pssm-sac)mentioning
confidence: 96%
“…We do not do this normalization which maintain the general total occurrence of the amino acids based on their substitution scores. Since we do not normalize by dividing it by length, it becomes implicitly a part of that feature (Taguchi and Gromiha, 2007;Sharma et al, 2013b;Dehzangi et al, 2013d).…”
Section: Semi Occurrence (Pssm-aao)mentioning
confidence: 99%
“…Thus, the bigram occurrence matrix B will consist of all the frequencies Bp,q. In this study, we have employed profile bigram because of its promising results [41,66,67,68,69,70,71,72,73]. Each bigram matrix B is then transformed to one feature vector as F=[B11,,Bij,,B3,3]T for i=1,2,3 and j=1,2,3, where superscript T denotes transpose.…”
Section: Methodsmentioning
confidence: 99%
“…This feature was introduced in [5, 89,86]. It was shown that information about the interaction of neighboring amino acids along the protein sequence can play an important role in providing significant local discriminatory information and enhancing protein subcellular localization prediction accuracy [6,87].…”
mentioning
confidence: 99%
“…This feature group is 145 directly extracted from PSSM matrix. It aims at capturing global discriminatory information regarding the substitution probabilities of the amino acids with respect to their positions in the protein sequence[85,86,87]. This feature is extracted by summation of the substitution score of a given amino acid with all the amino acids along the protein sequence.…”
mentioning
confidence: 99%